Insight Into Reduction of Wakefulness by Suvorexant in Patients With Insomnia: Analysis of Wake Bouts. Issue 1 (3rd November 2017) - Svetnik, Vladimir; Snyder, Ellen S; Tao, Peining; Scammell, Thomas E; Roth, Thomas; Lines, Christopher; Herring, W Joseph
Abstract: Study Objectives: To examine the duration and frequency of wake bouts underlying the wakefulness-after-sleep-onset (WASO) reduction with suvorexant. Methods: We analyzed polysomnogram recordings from clinical trials involving 1518 insomnia patients receiving suvorexant (40/30, 20/15 mg) or placebo to determine the following: (1) the number of, and time spent in, long or short wake bouts and (2) the association between sleep quality and bout characteristics. We also compared wake and sleep bout characteristics of suvorexant in insomnia patients versus zolpidem in healthy subjects undergoing experimentally induced transient insomnia. Results: Relative to placebo, suvorexant decreased the number and time spent in long wake bouts (>2 minutes) and increased the number and time spent in short wake bouts (≤2 minutes). The time spent in long wake bouts during Night-1 decreased by 32–54 minutes, whereas the time spent in short wake bouts increased by 2–6 minutes. On average, a patient returned to sleep from his or her longest awakening more than twice as fast on suvorexant than placebo. The reduced time spent in long wake bouts resulted in odds ratios of self-reported good or excellent sleep quality ranging from 1.59 to 2.19 versus placebo. The small increase in time spent in short wake bouts had no effect on odds ratios. Findings were more pronounced for the higher (40/30 mg) doses of suvorexant. The wake and sleep bout characteristics of suvorexant differed from zolpidem which equally decreased the number of wake and sleep bouts of all durations during the early part of the night. Conclusion: Suvorexant reduces WASO by reducing long wake bouts. This reduction has a positive effect on sleep quality. Clinical Trials: Trial registration at www.clinicaltrials.gov NCT01097616; NCT01097629.